1996
DOI: 10.1093/infdis/173.3.739
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Small Colony Variants Are Induced by the Endothelial Cell Intracellular Milieu

Abstract: Recent studies have reported that Staphylococcus aureus small colony variants (SCVs) can cause highly persistent infections in humans and in cultured endothelial cells. To understand the process by which SCVs of S. aureus appear in subjects who have not received antibiotic treatment, bovine endothelial cells were coincubated with a wild S. aureus strain for 72 h in the presence of lysostaphin. Intracellular bacteria were harvested and screened for stable SCVs. Intracellular bacteria developed the SCV phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
98
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(103 citation statements)
references
References 12 publications
5
98
0
Order By: Relevance
“…These studies led investigators at the time to speculate that both intracellular survival and extracellular multiplication play important roles in the pathogenesis of S. aureus infections (11). In this regard, recent experiments assessing invasion and intracellular survival of S. aureus in endothelial cells (16), epithelial cells (17), and osteoblasts (18) have suggested that intracellular survival could contribute to the persistence of the pathogen in S. aureus-induced endocarditis, bovine mastitis, and osteomyelitis. Although these in vitro studies speculate on the adaptive advantage of intracellular survival in nonprofessional phagocytes, no studies have assessed whether survival of S. aureus inside PMN occurs in vivo and whether this can promote infection.…”
mentioning
confidence: 99%
“…These studies led investigators at the time to speculate that both intracellular survival and extracellular multiplication play important roles in the pathogenesis of S. aureus infections (11). In this regard, recent experiments assessing invasion and intracellular survival of S. aureus in endothelial cells (16), epithelial cells (17), and osteoblasts (18) have suggested that intracellular survival could contribute to the persistence of the pathogen in S. aureus-induced endocarditis, bovine mastitis, and osteomyelitis. Although these in vitro studies speculate on the adaptive advantage of intracellular survival in nonprofessional phagocytes, no studies have assessed whether survival of S. aureus inside PMN occurs in vivo and whether this can promote infection.…”
mentioning
confidence: 99%
“…Biochemical characterization of the large majority of clinically isolated SCVs suggests specific defects in electron transport (25,35,36,49). Clinical and laboratory-generated S. aureus SCVs are frequently auxotrophic for menadione or hemin, two compounds required in the biosynthesis of the electron transport chain components menaquinone and cytochromes, respectively (1,3,4,25,35,36,46). Recently, electron-transportdeficient S. aureus SCVs were found to persist inside cultured endothelial cells (4).…”
mentioning
confidence: 99%
“…To determine the number of colony forming units (CFU), serial dilutions of the cell lysates were plated on Müller-Hinton (MH) and blood agar plates and incubated overnight at 378C. The colony phenotypes were determined on blood agar plates, recovered colonies were tested for the specific S. aureus clones (nuc-PCR, pulse field gel electrophoresis) and about 50 small or very small colonies were tested for auxotrophism as described (Vesga et al, 1996).…”
Section: Cell Culture Infection Modelsmentioning
confidence: 99%
“…Consequently, data on the development and dynamics of SCVs are largely missing. SCVs appear well adapted to the intracellular environment (Sendi & Proctor, 2009;Tuchscherr et al, 2010) and there are even some indications that SCVs could be induced by the intracellular milieu (Vesga et al, 1996). Further reported mechanisms leading to the formation of SCVs (in vitro and in vivo) include prolonged exposure to subinhibitory concentrations of antibiotics (Massey et al, 2001;Mitchell et al, 2010a;von Eiff et al, 1997a) or to exoproducts from other bacteria, e.g.…”
Section: Introductionmentioning
confidence: 99%